Adenylate Cyclase Toxin Tinkering With Monocyte-Macrophage Differentiation - Ahmad, Jawid Nazir; Sebo, Peter (Frontiers in Immunology, 2020)
Circulating inflammatory monocytes are attracted to infected mucosa and differentiate into macrophage or dendritic cells endowed with enhanced bactericidal and antigen presenting capacities. In this brief review we discuss the newly emerging insight into how the cAMP signaling capacity of Bordetella pertussis adenylate cyclase toxin manipulates the differentiation of monocytes and induces alveolar macrophage dedifferentiation to facilitate bacterial colonization of human airways.